Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament terhadap Minat Belajar Siswa pada Mata Pelajaran PAI - Pradita, Tarisa; Riza, Julianne Kamelia; Yanto, Ferry (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2026)
Student learning interest is one of the important factors that determine the success of the learning process, including in Islamic Religious Education (PAI). However, PAI learning still often faces the problem of low student learning interest due to the use of learning models that are less varied and tend to be teacher-centered. This study aims to analyze the effect of implementing the Teams Games Tournament (TGT) cooperative learning model on student learning interest in Islamic Religious Education at the senior high school level. This study uses a quantitative approach with a quasi-experimental design. The research subjects consisted of eleventh-grade students who were divided into an experimental class and a control class. Data on student learning interest were collected using a Likert scale questionnaire that had been tested for validity and reliability. Data analysis was carried out using descriptive statistics and inferential statistics through independent sample t-tests after fulfilling the prerequisite tests for normality and homogeneity. The results showed that there was a significant difference between the learning interest of students who participated in learning with the TGT model and students who participated in conventional learning. The average learning interest of students in the experimental class was higher than that of the control class, with a t-test significance value of less than 0.05. These findings indicate that the Teams Games Tournament cooperative learning model significantly increases students' interest in Islamic Religious Education. This study recommends the implementation of the TGT model as an innovative and participatory Islamic Religious Education learning alternative to increase students' interest in learning.